2018
DOI: 10.19080/ctbeb.2018.14.555876
|View full text |Cite
|
Sign up to set email alerts
|

Nigeria and the Selenium Micronutrient: A Review

Abstract: Local studies have documented the contributions of minerals to the health status of mammals. Selenium (Se) is an example of such minerals. It is essential for the activation and functioning of enzymes. In Nigeria, the mineral has been reported to be present in water, foods and soils. While the soil selenium concentrations determine selenium levels in foods, difference in food concentrations of the mineral atones for the variations in the plasma and tissue selenium level across the geopolitical zones of Nigeria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…This was much higher than the national prevalence of 35%. [21] High prevalence of selenium deficiency was also reported by other workers [32,33]. Selenium deficiency in this study was not associated with increased incidence, severity or LOH in children with pneumonia.…”
Section: Discussionsupporting
confidence: 84%
“…This was much higher than the national prevalence of 35%. [21] High prevalence of selenium deficiency was also reported by other workers [32,33]. Selenium deficiency in this study was not associated with increased incidence, severity or LOH in children with pneumonia.…”
Section: Discussionsupporting
confidence: 84%
“…The present results suggest that the levels of selenium in Nigerian staple foodstuffs (at least from the area studied) are sufficient for good nutrition. While this work was in progress, a review concerning selenium micronutrient appeared in Nigeria: the review reported results that generally agree with our data when expressed on an equivalent basis [25]. Thompson and Scott have shown earlier that 0.04 to 0.10 ppm selenium are needed in the diet to prevent selenium deficiency in chickens depending on the vitamin E content of the diet [26].…”
Section: Discussionsupporting
confidence: 81%
“…There are large differences in the reported levels of selenium in different studies, particularly the study by Muhammed et al [23], which reported serum selenium levels of 29 ng/dL in healthy individuals and 25 ng/dL in COVID-19-infected patients. This could be explained by the considerably low levels of selenium in soil in Nigeria [44].…”
Section: Discussionmentioning
confidence: 99%